Genetic Variability and Character Association in Taro (Colocasia esculenta (L.) Schott.) Under Mid-Hills of Arunachal Pradesh - Choudhary, V.K.; Suresh Kumar, P.; George, James; Kanwat, M.; Saravanan, R (JOURNAL OF ROOT CROPS, 2013)
An experiment was conducted to screen the superior taro genotypes and to identify the genetic divergence of quantitative characters under mid-hill conditions of Arunachal Pradesh. Fourteen taro genotypes were studied for their morphological, growth and yield characters. Taller plants were observed in APTC-1 (120.7 cm) followed by APTC-2. APTC-5 and TRC-2, which were on par in plant girth (17.8 cm) whereas greater number of suckers was seen in APTC-4 (4.5). Number of leaves (4), leaf area index (1.1-1.6), lamina length (24.8-37.2 cm) and breadth (17.8-28.6 cm) were more in APTC-2,APTC-7, APTC-1 and APTC-6 respectively. Cormel yield was significantly higher in APTC-5 (16.1 t ha-1) followed by Muktakeshi (15.1 t ha-1), APTC-1 (15.0 t ha-1) and APTC-2 (14.5 t ha-1), which were on par. The high value of Phenotypic Coefficient of Variation (PCV) along with Genotypic Coefficient of Variation (GCV) indicated that there was more variability in the characters like plant girth, number of side suckers, number of cormels and cormel yield. The high values of genetic advance (GA) coupled with high estimates of heritability suggest that real progress in improvement through selection could be made for yield and associated traits like number of leaves, lamina length and breadth, cormel weight and cormel size. The genotypes APTC-1, 2 and 5 and TRC-2 and 3 could be used for further breeding programmes.